Seasonal patterns in metazoan parasite community of the "Fat Sleeper" Dormitator latifrons (Pisces: Eleotridae) from Tres Palos Lagoon, Guerrero, Mexico - Violante González, Juan (2008)
Dormitator is among the most important fish genera in the Mexican Pacific coastal lagoon systems. In Tres Palos Lagoon, the Fat Sleeper Dormitator latifrons is one of the most significant species based on catch volume, although it is only consumed locally. Very little information exists on this species parasitofauna. Composition and temporal variation in the metazoan parasite community structure of Dormitator latifrons from Tres Palos Lagoon (99°47' W, 16°48' N), Guerrero, Mexico, were determined using seasonal samples taken between April 2000 and June 2002. Ten parasite species (55 817 individuals) were recovered from 219 examined hosts. These species included eight helminths (Ascocotyle (Phagicola) longa, Echinochasmus leopoldinae, Clinostomum complanatum, Pseudoacanthostomum panamense, Saccocoelioides lamothei, Parvitaenia cochlearii, Contracaecum sp. and Neoechinorhynchus golvani) and two crustaceans (Argulus sp. and Ergasilus sp.). Five of the helminth species exhibited seasonal variation in their infection dynamics associated with environmental changes during the dry and rainy seasons. The variations in the infection dynamics generated changes in the community structure over time.